2013
DOI: 10.1002/grl.50715
|View full text |Cite
|
Sign up to set email alerts
|

Observed variations in multidecadal Antarctic sea ice trends during 1979–2012

Abstract: [1] The spatiotemporal sensitivity of Antarctic sea ice season length trends are examined using satellite-derived observations over 1979-2012. While the large-scale spatial structure of multidecadal trends has varied little during the satellite record, the magnitude of trends has undergone substantial weakening over the past decade. This weakening is particularly evident in the Ross and Bellingshausen Seas, where a 25-50% reduction is observed when comparing trends calculated over 1979-2012 and 1979-1999. Mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
57
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(61 citation statements)
references
References 27 publications
4
57
0
Order By: Relevance
“…Previous studies have shown a positive trend in coverage and season length of sea ice in the Ross Sea and Weddell Sea regions (adjacent to Section 1) [1,34]. Both Sections 2 and 3 include areas of ice sheet, but the Bellingshausen/Amundsen Sea is adjacent to Section 1 and the Indian Ocean and Pacific Ocean are adjacent to Section 3.…”
Section: Spatial Trend and Classification Of Albedo Over Antarcticamentioning
confidence: 95%
“…Previous studies have shown a positive trend in coverage and season length of sea ice in the Ross Sea and Weddell Sea regions (adjacent to Section 1) [1,34]. Both Sections 2 and 3 include areas of ice sheet, but the Bellingshausen/Amundsen Sea is adjacent to Section 1 and the Indian Ocean and Pacific Ocean are adjacent to Section 3.…”
Section: Spatial Trend and Classification Of Albedo Over Antarcticamentioning
confidence: 95%
“…Over the period 1979-1990, the total Antarctic SIE decreased at a rate of −153 × 10 3 km 2 per decade (1.3% per decade), predominantly due to a rapid decline in the Bellingshausen Sea (e.g. [15]), although the trend in this short record is not significant. However, the decrease in ice seemed consistent at that time with the increasing concentrations of greenhouse gases and the loss of ice in the Arctic.…”
Section: The Observed Changesmentioning
confidence: 96%
“…The couplet of increasing SIE in the Ross Sea and decrease in the ABS is present in all seasons, although in winter the trend in the ABS is essentially zero. Furthermore, Simpkins et al [15] demonstrated that these trends are dominated by different temporal variability. Figure 1 shows that the largest positive SIC anomalies in the Ross Sea advance northwards during the sea ice growth season from close to the coast of Victoria Land in autumn to lie along the sea ice edge in spring, before retreating southwards again in summer.…”
Section: The Observed Changesmentioning
confidence: 99%
“…The polar regions have undergone major transformations over the last three decades, with satellite and in situ observations revealing a dramatic decline of Arctic summer sea ice extent and volume [Meier et al, 2013;Kwok and Rothrock, 2009], and a modest increase in winter Antarctic sea ice extent with significant spatial variability [Simpkins et al, 2013]. The magnitude and trends of such changes can only be partially captured by contemporary climate models [Stroeve et al, 2007;Jeffries et al, 2013;Tietsche et al, 2014], suggesting that important physical processes are being neglected.…”
Section: Introductionmentioning
confidence: 99%